Development of practicum guideline active compound isolation base on medical plant in Sasambo Society, Indonesia - A Wahab Jufri; Agus Ramdani; AA Sukarso; Jono Irawan; Aliefman Hakim (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2023)
The people of NTB have many distinctive cultures and cuisines. The use of plants is traditional medicine. This study aims to develop practical guidelines based on the medicinal plant sasambo, NTB. Development design is Research & Development with a 4D model (define, design, develop, and disseminate). The results of laboratory experiments are outlined in practicum guidelines for student activities. Chemistry lecturers in chemistry and natural product chemistry constructively validate the procedures. The analytical method uses Aiken's V formula and percentage agreement. The results of the expert validation show that the practicum guidelines meet very valid criteria with an Aiken value of 0.86. The guidelines also received positive responses from students and expert validators with an average practicality level of 88.6% with very practical criteria. Guidelines can be applied to learning with a percentage agreement of 100%. The cultural richness applied to learning can increase motivation learning and encourage students to be creative in developing products from the Sasambo milk medicinal plant.